2003
DOI: 10.1080/0144929031000120860
|View full text |Cite
|
Sign up to set email alerts
|

How the Web is used to support collaborative writing

Abstract: We present 19 systems that have been developed over the past decade to support collaborative writing over the Web. The aim of this article is to present the state of the art on the use of the Web for collaborative writing and thus (1) help designers improve current systems or define future systems, and (2) help users choose the most appropriate system to support their needs. Among available systems, groups can select from tools to write a document (on-or off-line), collect comments about a document, or maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Since an exhaustive review of such systems is beyond the scope of this paper, we refer the reader to review articles (e.g. Newman and Newman, 1992;Noël and Robert, 2003). The requirements of collaborative teams can be much more difficult than those for standalone software.…”
Section: Introductionmentioning
confidence: 98%
“…Since an exhaustive review of such systems is beyond the scope of this paper, we refer the reader to review articles (e.g. Newman and Newman, 1992;Noël and Robert, 2003). The requirements of collaborative teams can be much more difficult than those for standalone software.…”
Section: Introductionmentioning
confidence: 98%
“…55 Participants reported that their choice of editing directly versus commenting indirectly was related to the social status of the collaborator. For example, participants reported that they would not want to change their advisors' (or managers') words.…”
Section: Social Status and Expertisementioning
confidence: 99%
“…A study of tools for collaborative writing, including early Wiki software, is presented in [5]. The study shows, that the idea of splitting a document into fragments for different authors and propagating updates of these fragments to other authors is not new.…”
Section: Related Workmentioning
confidence: 99%
“…Various technologies and tools support either collaborative creation and evolution of documents (e.g. CSCW technologies, wikis or other Webbased collaborative writing applications [5]) or coordination of structured processes (e.g. BPM technologies like WfMS).…”
Section: Introductionmentioning
confidence: 99%